Effect of Funding Diversification on the Financial Performance of Nongovernmental Organizations in Kenya: A Case of Kenya Red Cross Society - Wakasa Nato Jacinta; Peter Gaiku (European Scientific Journal, ESJ, 2022)
Financial performance has been a matter of an on-going concern for non-governmental organizations, with scarcity of resource and mounting societal needs. The enduring problem has been on how to attain financial sustainability and reduce over-dependency on donor funding. It is hypothesized that engaging in funding diversification will enhance financial performance of non-governmental organizations. The main aim of this research was to examine the effect of funding diversification on financial performance of non-governmental organizations in Kenya. Stakeholder theory and resource dependency theory were adopted to anchor the study. A descriptive research design was used in this research. The population of the study were the 10 Kenya Red Cross Society departments in Nairobi. The unit of observation was the 389 employees in these departments. Sample size was 198 employees stratified according to their departments. Primary data was collected using questionnaires. The questionnaires were administered through emailing as well as drop and pick later method. Upon collection of the data, it was coded in quantitative format so as to enable analysing through use of statistical package for social sciences (SPSS) version 24. Descriptive and inferential statistics generated were presented in tables and figures. The correlation findings showed that the relationship amongst funding diversification and financial performance was positive (r=0.429, p<0.001). The regression coefficient results indicated that funding diversification positively and significantly affected financial performance (β=0.558, p=0.000). This suggested that a unit increase in funding diversification would result in 0.558 increase in financial performance. This study concluded that funding diversification is an essential practice for NGOs to use in their endeavor to improve on their financial performance. The study recommends that management of NGOs should implement funding diversification in their operations to enhance financial performance.